2018
DOI: 10.3233/jin-170025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high fat diet and perinatal dioxin exposure on development of body size and expression of platelet-derived growth factor receptor β in the rat brain

Abstract: Environmental exposure to dioxins, consumption of a high fat diet, and platelet-derived growth factor receptor β signaling in the brain affect feeding behavior, which is an important determinant of body growth. In the present study, we investigated the effects of prenatal exposure to 2,3,7,8-tetrachlorodibenzo-p-dioxin and high fact diet after weaning on body growth and expression of platelet-derived growth factor receptor β in the brain in rat pups. Subjects from the control and dioxin exposure groups were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…[ 20 ] Similar to age‐associated cerebrovascular phenotype, HFD also causes cerebrovascular impairment [ 22 ] and PDGF‐BB/PDGFR β signaling alteration in the brain. [ 23 ] We therefore assessed cerebrovascular changes in mice fed HFD. Consistently with our previous finding, elevated concentration of PDGF‐BB was also detected in both serum and plasma of mice fed HFD relative to the mice fed normal CHD, with 4.9‐fold and tenfold increase in serum and plasma, respectively (Figure S3A,S3B , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 20 ] Similar to age‐associated cerebrovascular phenotype, HFD also causes cerebrovascular impairment [ 22 ] and PDGF‐BB/PDGFR β signaling alteration in the brain. [ 23 ] We therefore assessed cerebrovascular changes in mice fed HFD. Consistently with our previous finding, elevated concentration of PDGF‐BB was also detected in both serum and plasma of mice fed HFD relative to the mice fed normal CHD, with 4.9‐fold and tenfold increase in serum and plasma, respectively (Figure S3A,S3B , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Further studies to establish if this could be generalized to other opioids remain necessary. For example, PDGFRβ is also expressed in brain regions involved in reward and addiction such as mPFC, NAc and dStr ( Balayssac et al, 2009 ; Bor et al, 2017 ) and PDGFRβ levels were shown to be altered in the striatum and midbrain of rodents with disrupted dopaminergic signaling, a central component for reward signaling ( Masuo et al, 2004 ). Overall, this work suggests RTKs could be promising, yet understudied, candidates to mitigate morphine reward, especially IRs.…”
Section: Involvement Of Receptor Tyrosine Kinase Signaling Opioid-med...mentioning
confidence: 99%
“…Animal studies have reported that dioxin exposure affected brain regions in the limbic system such as the hypothalamus, nucleus accumbens, amygdala, and orbitofrontal cortex [ 13 16 ] that are involved in controlling appetite and food rewards [ 17 , 18 ], and altered taste preference in female rats exposed to dioxin perinatally [ 19 ]. Based on these findings, we hypothesized that dioxin may alter eating behaviors in children perinatally exposed to dioxin by affecting these brain regions.…”
Section: Introductionmentioning
confidence: 99%